EFFECT OF N AND K FERTIGATION LEVELS ON TOTAL FRUIT YIELD, YIELD ATTRIBUTES AND WATER PRODUCTIVITY OF PAPRIKA (Capsicum annuum.L) - B. NEERAJA PRABAKAR, D. MOUNIKA, M. UMA DEVI, V. PRAVEEN RAO, K. AVIL KUMAR and (The Journal of Research, PJTSAU, 2019)
Fertigation is a frontier technology, which permits application of various nutrients and fertilizer formulations directly at the site of active roots in desired concentration, time and thus improves the nutrient use efficiency and the yield of crops. Paprika (Capsicum annuum L.) is a less pungent widely used chilli variety and is an important vegetable cum condiment and is used as an ingredient in a broad variety of dishes throughout the world. There is a need to study the vital aspects of fertigtion for different crops involving the sources of fertilizers, rate of fertilizers, frequency of fertigation, methods of fertilizer application through soil, drip irrigation, combination of soil and irrigation water and combination of nutrients for fertigation etc.